EFFECT OF HUMID TROPICAL CLIMATE ON FRICTION CHARACTERISTIC OF PNEUMATIC CYLINDERS: Effect Of Humid Tropical Climate On Friction Characteristic Of Pneumatic Cylinders - Nguyen, Thuy; Pham, Van Hung (Journal of Applied Engineering Science, 2021)
The pneumatic cylinder is influenced by many various factors at work, including the climate environment. The climatic environment consists of two characteristic factors as temperature (T) and relative humidity (RH), which change according to seasons and different geographical regions. Therefore, changing the climate characteristic factors will affect the friction characteristic of pneumatic cylinders when operating at different speeds. This article presents empirical research on the simultaneous effects of temperature and relative humidity of the environment with the humid tropical climate in Vietnam on the pneumatic cylinder’s friction properties. According to experimental planning, the studies were conducted on industrial pneumatic cylinders with two input factors: the temperature of 150C, 320C and 490C and relative humidity of 51%, 75% and 99%, with velocities of 30, 50 and 100 mm/s. The results show that the static friction force and dynamic friction decrease when T, RH increases, and the influence of air relative humidity on friction force is more significant than temperature. The experiment also gives an empirical regression equation on the relationship of friction in the pneumatic cylinder, depending on the two factors of temperature and relative humidity of the humid tropical climate in Vietnam with velocities of 30, 50 and 100 mm/s.